Needs Analysis of Electronic Story Calendar Media to Improve Spirit of Nationalism - Ambarsari, Ria; Sartono, E Kus Eddy; Mustadi, Ali; Zubaidah, Enny; Jhon, Winarni; Rafsanzani, Muhammad Akbar (LPPM Undiksha, 2021)
The coronavirus (Covid-19) outbreak which has hit countries worldwide, presents its educational landscape challenges, especially elementary schools. Therefore, online learning requires the availability of various learning facilities and infrastructure that support online learning, for example, electronic devices and internet connections. This situation makes teachers and students learn to recognize and apply various kinds of technology in online learning. Teachers and students must also be familiar with observing, exploring and playing with technology in their learning and daily activity. This study aims to identify and analyze instructional media that need to be developed and optimized for fifth-grade students in Elementary School. This research implemented a mixed-method design with a qualitative and quantitative approach and the explanatory model. We distributed a questionnaire towards 121 students through Google Forms and also interviewed nine teachers and nine students. We found that: (1) regarding needs for the development instructional media to improve reading comprehension skills, 45% teachers agreed that it was very necessary and 64% students agreed that it was necessary, (2) regarding interest towards electronic story calendar media, 56% teachers agreed that it was interesting and 49% students agreed that it was very interesting, and (3) regarding needs for the development of electronic story calendar media about the national hero, 56% teachers agreed that it was very necessary and 50% students agreed that it was necessary.